Numerical and Experimental Thermal-Hydraulic Performance Analysis of a Supercritical CO2 Brayton Cycle PCHE Recuperator - Arslan, Feyyaz; Guzel, Bulent (SPRINGER HEIDELBERG, 2021)
The supercritical carbon dioxide (s-CO2) power cycles are mostly preferred due to their high thermal efficiency and power density in comparison with the conventional steam Rankine cycles. In this study, a printed circuit heat exchanger recuperator which is an important component in s-CO2 recuperative Brayton cycles is numerically and experimentally examined. Within this scope, thermal-hydraulic and structural analyses of a proposed PCHE have been carried out. The sub-heat exchanger model, which uses the output of a sub-heat exchanger as the input of the next one, is applied in the numerical thermal-hydraulic design by subdividing the printed circuit heat exchanger. From the results of this analysis, a heat exchanger is structurally designed and fabricated in compliance with ASME BPVC rules. The fabricated 25 kW printed circuit heat exchanger has reached to 1000 m(2)/m(3) compactness value with 1 mm thickness of fin and 1.5 mm thickness of plate. The experiments were performed on a test bench working with supercritical carbon dioxide at high pressures. The results of the experimental and numerical analyses are in good agreement. The maximum difference between the heat loads and the effectiveness values is 4.9% and 5.4%, respectively. The difference between the overall heat transfer coefficients is 1.2%. It is shown that using the sub-heat exchanger model provides highly accurate printed circuit heat exchanger designs.
Keywords: Supercritical; PCHE recuperator; Thermal– hydraulic analysis; Compact heat exchanger; WHRS; Printed circuit heat exchanger; Science & Technology - Other Topics